A quantitative analytical investigation on the oxycodone side effects listed in recent clinical trials - Farshad Ghassemi Toosi; Alireza Ghassemi Toussi (European Journal of Translational and Clinical Medicine, 2023)
Background: Oxycodone is a semi-synthetic narcotic analgesic medication with numerous side effects. Patients who use oxycodone may have one or more side effects depending on their clinical status and/or other factors. Our aim was to analyze clinical trials for any potential pattern related to the side effects of oxycodone.